SMART STEPS FOR GREAT MOTHERS: RAISING CHILDREN FREE FROM STUNTING - Subriah Subriah; Ade Devriany; Agustina Ningsi; Ros Rahmawati; Hidayati Hidayati; Asmawati Gasma (Bajang Institute, 2026)
Stunting remains a major public health problem that can adversely affect children's physical growth, cognitive development, productivity, and quality of life in the future. Stunting prevention should be initiated during the first 1,000 days of life through improving mothers’ knowledge and skills regarding nutritional fulfillment, breastfeeding practices, and reproductive health. The Community Service Program (PkM) entitled “Smart Steps for Great Mothers: Raising Stunting-Free Children” aimed to enhance the knowledge and skills of women in the interpregnancy period, postpartum mothers, and breastfeeding mothers in preventing stunting. The program was conducted on April 19, 2026, at Nuhrintama Clinic, Gowa Regency, involving 15 participants. The methods included health education sessions, breastfeeding technique demonstrations, family planning counseling, and psychosocial support. Evaluation was carried out using pretest and posttest assessments to measure changes in participants’ knowledge. The results demonstrated an improvement in participants’ knowledge following the intervention. During the pretest, 9 participants (60%) had good knowledge, while 6 participants (40%) were categorized as having poor knowledge. After the intervention, the posttest results showed a significant increase, with 13 participants (86.67%) demonstrating good knowledge and only 2 participants (13.33%) remaining in the poor knowledge category. In addition, 85% of participants were able to correctly demonstrate breastfeeding positions and proper latch-on techniques after attending the demonstration and simulation sessions. During family planning counseling, three participants expressed their willingness to use Long-Acting Reversible Contraceptive Methods (LARCs), namely contraceptive implants and intrauterine devices (IUDs). The program also strengthened interprofessional collaboration among lecturers, students, midwives, and nurses in delivering comprehensive health education services. This community service program was effective in improving mothers’ knowledge, skills, and awareness regarding stunting prevention through exclusive breastfeeding, proper breastfeeding techniques, appropriate complementary feeding practices, and optimal birth spacing. Similar programs should be implemented continuously to support efforts to accelerate stunting reduction within the community.